The World Book student discovery encyclopedia : M (second edition) (World Book Chicago, 2007)
"A 13-volume, illustrated, A-Z general reference encyclopedia for students with high interest, low reading levels, providing traditional features of adult reference works, plus activities, atlas of world maps, special articles, and cumulative index"--Provided by publisher